2012
DOI: 10.5491/shaw.2012.3.2.140
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Miners Relocated to Alternative Positions due to Silicosis in the Andean of CODELCO, Chile, 2010

Abstract: ObjectivesTo understand the personal experiences of mine workers that have experienced job relocation due to silicosis at the Andina Division of Corporación Nacional del Cobre (CODELCO), Chile. The purpose of the study was to provide useful information for the development of new local, business and public policies for the care of workers with silicosis.MethodsA qualitative study based on a practical case study of 5 workers. The information was collected by means of structured individual interviews. The method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
5
0
3
Order By: Relevance
“…Thus, the relationship between the index of chronic obstructive pulmonary disease (the Tiffenau index) and body weight was studied. Several risk factors, related to obesity and metabolic disorders, may be identified for the investigated job category: shift work and night shifts with irregular shifts [8] and alterations in lung function [17,18]. In Tables 3 and 4, it may be observed that in the highest mine, the lowest oxygen saturation levels…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, the relationship between the index of chronic obstructive pulmonary disease (the Tiffenau index) and body weight was studied. Several risk factors, related to obesity and metabolic disorders, may be identified for the investigated job category: shift work and night shifts with irregular shifts [8] and alterations in lung function [17,18]. In Tables 3 and 4, it may be observed that in the highest mine, the lowest oxygen saturation levels…”
Section: Discussionmentioning
confidence: 94%
“…Finally, we investigated the effects of shift work, and especially night work. We focused on major effects suggested by literature, i.e., the metabolic and respiratory ones [8,17,18]. Thus, the relationship between the index of chronic obstructive pulmonary disease (the Tiffenau index) and body weight was studied.…”
Section: Discussionmentioning
confidence: 99%
“…Current limited molecular knowledge regarding Se and fibrogenic dust might be one of the reasons justifying why Se has not been widely studied in this area, and why Se supplementation is not recommended in routine care to prevent or delay the onset of pneumoconiosis or malignancies in individuals exposed to fibrogenic dust. As recently highlighted by Delgado et al (2012), relocation of workers exposed to fibrogenic dust to other jobs after disease development is an important strategy of secondary or tertiary prevention of dust related diseases. Along these lines, it would be meaningful for relocated workers to be assessed individually, since individuals with lower Se status might benefit from Se supplements in order to enhance the effects of other treatment strategies, as it has been reported that genotoxic and fibrogenic effects of mineral dust can lead to the development of lung cancer (Tsuda et al, 2002), and Se might protect against lung cancer (Fritz et al, 2011;Zhuo et al, 2004).…”
Section: Authormentioning
confidence: 99%
“…2 No obstante pueden existir riesgos asociados a la propia actividad e independientes del tipo de esterilización que se lleve a cabo, como pueden ser la manipulación de cargas o los movimientos repetitivos 3 , los diferentes procesos para conseguir esterilidad conllevan una serie de peligros inherentes a la propia naturaleza del proceso que van desde quemaduras asociadas a las altas temperaturas hasta el carácter cancerígeno y mutágeno de algunos de los agentes esterilizantes químicos. [4][5][6][7] Por lo tanto, teniendo en cuenta la importancia y la complejidad de esta práctica y la escasez de publicaciones sobre el tema, se realizó este estudio, cuyo objetivo fue evaluar el conjunto de factores relativos a las condiciones del trabajo que pueden tener repercusiones sobre la salud y la calidad de vida en el trabajo de las auxiliares de esterilización, más aun si se enfatiza que la calidad de vida en el trabajo [8][9][10][11] es una filosofía que dignifica al trabajador y su desarrollo personal.…”
Section: Introductionunclassified